Penguatan Perilaku âNgeloni Anakâ Oleh Ibu-Ayah sebagai Upaya Menciptakan Keluarga Harmonis-Seimbang Sejak Dini - Rahmatullah, Azzam Syukur (IAIN Ponorogo, 2016)
One of important aspects in educating children to have a harmonious, balanced, and lasting family is to concern on parenting since early times. One of the ways is to hug a child. This paper discusses the importance of child development so they can build a harmonious family. When the parent demonstrates their affections to their children by hugging, the children will get a double touch from their parent (father and mother) and they do not get the touch from one of them. Hugging children has a big role to child development in the future. The more the parent gives a sincere affection, positive situation, friendship, the more children will get strong of personality. A good and health personality will affect self-children positively when they build a family to become a harmony family. On the contrary, the less the parent give a warm hugging likes no affections and sincerity, derision, insult and reproach; the more the children will get a sick personality. Such personality will be a problem for children either in the present times or during the development period from childhood to teenage and adult.Â Ø£ØØ¯ Ø§ÙØ¬ÙØ§ÙØ¨ Ø§ÙÙØ§Ù Ø© Ø§ÙÙ Ø¤Ø¯ÙØ© Ø¥ÙÙ Ø£Ù ØªÙÙÙ Ø£Ø³Ø±Ø© Ø§ÙÙÙØ¯ ÙÙ Ø§ÙÙ Ø³ØªÙØ¨Ù Ø£Ø³Ø±Ø© Ø³Ø¹ÙØ¯Ø© Ù Ø³ØªÙØ±ÙØ© ÙÙÙ Ø¯ÙØ§Ù ÙÙ Ø§ ÙÙ ÙÙ Ø· Ø§ÙØØ¶Ø§ÙØ© Ø§ÙØµØÙØØ© Ù ÙØ° Ø§ÙØ¨Ø¯Ø§ÙØ©. Â ÙÙ Ù ÙÙÙÙØ§Øª Ø§ÙØØ¶Ø§ÙØ© ÙØ§ÙØªØ±Ø¨ÙØ© ÙÙ ØªØØ¶ÙÙ Ø§ÙÙÙØ¯ ÙÙ Ø¹Ø§ÙÙØªÙ. ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ© ÙÙØ§Ø´ Ø£ÙÙ ÙØ©